Prospective study on outcomes of postpartum intrauterine contraceptive device including safety, efficacy and expulsion at GMERS Medical College, Dharpur-Patan, Gujarat, India - Jani, Parul S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Evaluation of PPIUCD in terms of incidence of failure, expulsion, bleeding pǎnd other complication. Present study is aimed at determining the safety, efficacy, expulsion of post placental and intra cesarean insertion of intrauterine device. Methods: Prospective analysis was carried out to collect information regarding IUCD insertion and outcome at tertiary care center for the period of three years using the hospital record that a total number of 600 mothers had postpartum intrauterine contraceptive device. Results: Total women opted for PPIUCD 600, Followed up 560 after 1 week, 580 after 6 weeks and 400 after 6 months. Complications after 6 months 228. (pain 66, bleeding 37, expulsion 17, strings problem 7, discharge p/v 101). Conclusions: The insertion of PPIUCD is safe and effective method of contraception in the means of complication though it is a new concept for the population it is well accepted by the community though expulsion rate is somewhat high compare to conventional IUCD. it can be reduced with practice.